What are the neural correlates of dissociative amnesia? A systematic review of the functional neuroimaging literature - Taïb, Simon; Yrondi, Antoine; Lemesle, Béatrice; Péran, Patrice; Pariente, Jérémie (Frontiers in Psychiatry, 2023)
Aim: Dissociative amnesia is an emblematic psychiatric condition in which patients experience massive memory loss ranging from focal to global amnesia. This condition remains poorly understood and this review aims to investigate the neuroanatomical feature of this disease. Methods: We conducted a systematic review of the scientific literature available on PubMed, up to December 1, 2022, using a combination of keywords referring to dissociative amnesia. We included every scientific report involving patients undergoing a functional imaging procedure. Results: Twenty-two studies met our inclusion criteria (gathering 49 patients). Only one was a controlled study with a large sample. The other 21 were case reports and case series. In resting state, neuroimaging studies mostly showed a hypo-activated right inferolateral prefrontal cortex, associated with limbic hypoactivity and lesser activation of the hippocampal and para-hippocampal structures. The patients also presented abnormal patterns of cerebral activation when performing memory tasks. When testing recognition of memories from the amnestic period, patients showed increased activation across temporal areas (hippocampal and para-hippocampal gyri) and the limbic network. When trying to recollect memories from an amnestic period compared to a non-amnestic period, patients failed to activate these structures efficiently. Most of these patterns tended to return to normal when symptoms resolved. Conclusion: This review identified a paucity of controlled studies in the field of dissociative amnesia neuroimaging, which restricts the extrapolation of results. Patients with dissociative amnesia present a broad prefronto-temporo-limbic network dysfunction. Some of the brain areas implicated in this network might represent potential targets for innovative treatments.